Speech Acts Reflected in Emma Watson’s Speech: An Analysis and Its Implications in Teaching Listening - Nur Ekawati, Yulia; Defika, Chintara; Sumartono, Sumartono (LPPM Universitas Pancasakti Tegal, 2020)
The message of a speech will be achieved by audiences if the use of speech acts is appropriate with its purposes. There are three types of speech acts; i.e. locutionary, illocutionary, and perlocutionary. This study aims to know the speech acts used in Emma Watson’s speech delivered about feminism and explore its implications in teaching listening comprehension. Emma Watson tend to bring her audience, especially men to join her campaign, called HeForShe. It has successful reach the world’s attention to end the gender inequality because of her powerful speech. To collect the data, a speech transcript was provided and analyzed. The qualitative descriptive research is used in order to investigate the implementation of locutionary, illocutionary, and perlocutionary used in the speech. The result showed those three types of speech acts were used. In addition, the illucationary act of Assertive shown for 76,74%. It indicates that this speech contained opening, informing, convincing, insisting, and clarifying. This results have the implications in teaching listening such as delivering the materials of teaching could be started from listening words by words, looking for the meaning of difficult words, informing the content of text, giving respond, and achieving the meaning of text. The teacher suggested to use this speech as one of material in teaching listening by considering its objectives of teaching.